1992
DOI: 10.1111/j.1540-8191.1992.tb00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutaraldehyde-Fixed Bovine Iliac Veins Used as Bioprosthetic Conduits: An Experimental Animal Study

Abstract: The ideal prosthetic conduit for surgical repair of complex congenital heart disease has yet to be found. Twenty conduits were implanted between the right ventricle and pulmonary artery in growing sheep as follows: four Dacron porcine valve conduits (mean time in place, 142 days); four avalved glutaraldehyde-fixed bovine iliac veins (mean 132 days); and 12 glutaraldehyde-fixed bovine iliac veins containing a porcine valve (mean 180 days). Fifteen conduits were left in place from 167 to 244 days (mean 204 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A common approach for increasing the strength of biologic scaffolds composed of ECM or components of ECM (e.g., purified type I collagen) has been the use of chemical crosslinking agents such as CDI, 24,[32][33][34] isocyanate, 49 or glutaraldehyde. [50][51][52] While chemical crosslinking does maintain the mechanical strength of the scaffold, it also necessarily alters the kinetics of degradation and has a deleterious effect on the biologic activity of the degradation products. The present study showed that CDI effectively inhibited ECM scaffold degradation regardless of the presence of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…A common approach for increasing the strength of biologic scaffolds composed of ECM or components of ECM (e.g., purified type I collagen) has been the use of chemical crosslinking agents such as CDI, 24,[32][33][34] isocyanate, 49 or glutaraldehyde. [50][51][52] While chemical crosslinking does maintain the mechanical strength of the scaffold, it also necessarily alters the kinetics of degradation and has a deleterious effect on the biologic activity of the degradation products. The present study showed that CDI effectively inhibited ECM scaffold degradation regardless of the presence of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous reports have demonstrated a vascular xenograft crosslinked with glutaraldehyde in the reconstruction of small caliber biological vessels, such side effects as degeneration, aneurysm formation, and cytotoxicity related to use of glutaraldehyde have remained clinical problems ( 7–9). Recently, however, a polyepoxy compound has been introduced as a new crosslinking agent to overcome the aforementioned disadvantages of glutaraldehyde ( 9–12).…”
Section: Discussionmentioning
confidence: 99%
“…The glutaraldehyde solution itself is known to have possible genetic side effects. Additionally, the development of ectopic calcification and the tendency to make tissue less flexible, more hydrophobic, and less adaptable to the host tissue, as well as aneurysm formation and cytotoxicity, have all been implicated in the use of glutaraldehyde as a fixative agent ( 7, 8). To overcome these disadvantages, polyepoxy compounds have been introduced as new crosslinking agents and have been found to be more suitable for this purpose than glutaraldehyde ( 9–12).…”
mentioning
confidence: 99%
“…Besides autologous pericardium, which is often unavailable due to previous operations, implants used are made of synthetic materials such as Dacron (based on Polyethylenterephtalate) or Gore-Tex (based on polytetrafluoroethylene) and biological materials like glutaraldehyde-fixed bovine pericardium [3,4]. A limitation of these implants is that they are permanent foreign bodies with the potential for infection and the absence of remodeling, regeneration, and growth potential [5,6]. Furthermore, the glutaraldehyde-treated material shows early deterioration and should ideally be avoided in young patients [7].…”
Section: Introductionmentioning
confidence: 99%